Spinovalva gen. nov., a new genus for Gelechia delodectis Meyrick, 1938 (Lepidoptera, Gelechiidae) - Bidzilya, Oleksiy (Zootaxa, 2022)
A monotypic genus Spinovalva gen. nov. is introduced to accommodate “Gelechia” delodectis Meyrick, 1938. The new genus is placed in the subfamily Anomologinae and compared with Gladiovalva Sattler, 1960. The adult, male and female genitalia of Spinovalva delodectis (Meyrick, 1938) comb. nov. are redescribed based on examination of its type specimen and additional sympatrically collected specimens of both sexes. The lectotype of Gelechia delodectis Meyrick, 1938 is designated.